Implementation of P5 in the Independent Curriculum in the Fifth Grade of SDN 3 Jerukwangi - Rizki, Atik Eva Nur; Attalina, Syailin Nichla Choirin; Hamidaturrohmah, Hamidaturrohmah (EduBasic Journal: Jurnal Pendidikan Dasar, 2024)
This study focuses on the implementation of the Pancasila Student Profile Strengthening Project (P5) at SDN 3 Jerukwangi, with the theme “Sustainable Lifestyle.” This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) and its impact on students, especially in increasing their environmental awareness and creativity. This study used a qualitative methodology with a case study approach. Data was collected through observation, interviews with homeroom teachers and principals, and a survey of five fifth-grade students who participated in the P5 activity. The results of this study revealed that the implementation of P5 went well, with students actively involved in all stages of the project, from planning to making Ecobrick products from plastic waste. This project succeeded in increasing students’ environmental awareness and creative skills in managing waste. The main supporting factors include the involvement of students and parents, teacher support, and infrastructure. This study concludes that P5 at SDN 3 Jerukwangi achieved its goal of forming students’ characters who care about the environment and are creative and responsible. This study also recommends closer collaboration between schools, students, and parents in supporting future project implementation.